The Link Between Obesity and Periodontitis Severity: A Population-Based Study: Life Sciences -Dentistry - Ramya, Dr V.; Amaldas, Dr Julius; J Bhuvaneswarri, Dr (International Journal of Life Science and Pharma Research, 2023)
Obesity contributes to an overall inflammatory condition through its metabolic and immune parameters, therebyincreasing susceptibility to periodontal disease and periodontitis being one of the most common chronic inflammatory diseases.Therefore, by evaluating the risk variables for Obesity and periodontitis, we could know the association, influence, and severityof Periodontal disease. 150 individuals reported to the Department of Periodontics, SBDCH, who were more than 35-70 yearsof age with mild, moderate, and severe Periodontitis were included in the study. A clinical examination was performed, whichincluded height, weight, waist circumference, abdominal/hip circumference, and blood pressure. On Intra oral examination,bleeding on probing, Periodontal probing pocket depth, and clinical attachment level was measured to assess the severity of theperiodontal condition. In addition, a blood investigation of lipid profile and HbA1C was taken. We found a statistically significantassociation between metabolic syndrome and Periodontal status. Obesity influences the severity of Periodontitis, and it's apopulation-based cross-sectional study; all the independent risk variables have a major role in developing the risk ofperiodontitis. Periodontitis has been proposed to contribute to systemic conditions such as cardiovascular disease primarilythrough the inflammatory and microbial burden posed by the inflamed surface area of the periodontal pocket.